Financial leasing in Albania and the impact that internal factors of a SME would have on the probability to be financed by lease - Fatjola Lubonja; Blerina Gjylameti; Sllavka Kurti (Central European Economic Journal (CEEJ), 2019)
Small- and medium-sized enterprises (SMEs) are the backbone of the economy and their need to be financed remains one of the most discussed topics in the business world (World Bank, 2014; IFC, 2010). Financial leasing is a midterm financial instrument mainly used for the procurement of machinery, equipment, tools and/or property (IFC, 2009). Although the financial leasing in Albania started in 2001, this form of business financing has experienced difficulties in spreading, getting recognised and being used by the public in Europe which is different from other countries. About 19 years after the creation of the first leasing companies, this financing option continues to be used at a low scale by businesses and individuals and it remains segmented into the market despite its large potential and the need for financing similar to SMEs. Why is financial leasing not yet used in Albania and which are some of the factors that would influence its use in the future? The purpose of this article is to identify the reasons of why the financial leasing market in Albania is in stagnation and understand some of the factors that influence the demand from a SME to be financed through lease. To achieve this and understand firms' behaviour, questionnaire has been distributed to companies that have used lease to finance their asts and those that have never used it before. The model used to analyse the results of the questionnaires is the logistic regression. As we will see through the article, factors in need for financing by SMEs or the knowledge firms have about leasing have a direct impact on the possibility of firms to use lease.
Keywords: G23; G40; G41; H70; D22; 330; leasing; SMEs; finance; leasing market; leasing companies; conduct of businesses